Gradient light interference microscopy for 3D imaging of unlabeled specimens - Tan H. Nguyen (Nature Portfolio, 2017)
Challenges in biological imaging include labeling, photobleaching and phototoxicity, as well as light scattering. Here, Nguyen et al. develop a quantitative phase method that uses low-coherence interferometry for label-free 3D imaging in scattering tissue.